Telecontrolling pada Kandang Jangkrik Berbasis IoT (Internet of Things) - a Anshar; Lis Diana Mustafa; Nugroho Suharto (Jurnal Jaringan Telekomunikasi, 2021)
Cicadas are a unique type of insect, have a distinctive sound and are active at night, Cicadas are widely cultivated by the community because they can support the community's economy both for pet feed, animal feed mixtures, food additives to cosmetic mixtures. Aspects that need to be considered in the cultivation of Cicadas, namely environmental factors that affect the life and growth of Cicadas daily are from sources of nutrition, temperature and humidity. DHT22 and RTC sensors to measure temperature and humidity in the cricket cage and RTC to detect time. The sensor data input will be processed by ESP32 which is a System on Chip with Wi-Fi and Bluetooth, then detected by Fuzzy Logic to determine the activation output and when the Cicadas are harvested will be sent via the telegram application. The results of the system design for control and monitoring have been successfully implemented in the cricket cage based on temperature, humidity and time. The system can send output notifications and responses in accordance with predetermined conditions with the telegram application and data storage on the website. Testing the accuracy of the sensor gets a fairly accurate presentation of accuracy, that is, on average the percentage accuracy of temperature gets 98% and at humidity it gets a value of 97%, and Testing the results of the percentage of accuracy on the system and fuzzy simulation using telegram and matlab applications gets a percentage value 31.66% accuracy.